Prevalence and Associated Risk Factors for Post-Traumatic Stress Disorder (PTSD) in COVID Survivors: A Cross-Sectional Study - Dhakal, Surakshaya; Khatiwada, Ram Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background The COVID-19 pandemic has caused widespread physical and psychological health challenges. In Nepal, research on the mental health consequences, especially post-traumatic stress disorder (PTSD), among COVID-19 survivors remains limited. This study aimed to find the prevalence and associated risk factors of for Post-Traumatic Stress Disorder (PTSD) in COVID Survivors. Methods A cross-sectional study was conducted with 228 COVID-19 survivors in Damak COVID Hospital from April to October 2022. Ethical approval was taken from IRC of Institute of Science and Technology, Tribhuvan University (Ref. No. 46/079/080). Data were collected using standardized questionnaires. Data was analyzed using descriptive and inferential statistical tools using SPSS-16. After bivariate analysis, Binary logistic regression was carried out among the significant variables. Model validity was confirmed through Pseudo R², Hosmer-Lemeshow, reliability, and multicollinearity tests. P-value<0.05 was considered as statistically significant. Results The prevalence of PTSD among survivors was 40.4% (with 95% CI as 34.03% to 46.76%). Significant predictors included gender, diabetes, and chronic obstructive pulmonary disease (COPD). Females were more likely to experience PTSD symptoms than males. Diabetes, whether present before or developed after COVID-19, increased PTSD risk. High blood pressure before infection and COPD developed post-COVID were also linked to higher PTSD likelihood. The logistic model explained 40.2% to 54.2% of the variance in PTSD symptoms. Conclusions The prevalence of PTSD was high among the COVID Survivors in the Damak area of Jhapa Nepal. Age, Diabetes, High Blood pressure and COPD key risk factors for PTSD. These findings emphasize the need for targeted mental health interventions to support vulnerable groups and address the psychological aftermath of COVID-19, ultimately improving survivor well-being.